Lawrence of Arabia (1962): A Tragic Hero in an Ever-Lasting Quest - Barbudo, Maria Isabel, 1950- (2014)
Being based on a real-life historical hero — T. E. Lawrence, who fought side by side with the Arabs in the First World War — the cinematographic adaptation of his work Seven Pillars of Wisdom directed in 1962 by David Lean and with a screenplay by Robert Bolt gives us the portrait of an eminently tragic hero. Admitting that his heroic status in the film is by no means clear-cut, this paper aims at demonstrating that he nevertheless displays the main features of the typical tragic hero, as presented in the ancient Greek tragedies. The quest he is pursuing relates, on the other hand, to the history of a region that, until nowadays, has been continually torn by conflicts rooted in the First World War and its aftermath.